Evaluation of NiO supported on waste sludge for the degradation of 2- chlorophenol - Sharifah Nurafiqah, Syed Kamarularifin; Nornasuha, Abdullah; Hamidah, Abdullah; Nurul Aini, Razali (Elsevier Ltd, 2023)
Due to the harmful consequences for the environment and human health, chlorophenol is regarded as a hazardous pollutant. This study aims to utilize waste sludge material loaded with NiO (NiO/sludge) as a cost-effective adsorbent for the treatment of 2-Chlorophenol (2-CP). The properties of the NiO/sludge were determined by FTIR and XRD analysis. In a batch study of 2-CP degradation, the effectiveness of NiO/sludge was assessed under a variety of conditions, including pH solution (2–8), temperature (28–50 °C), 2-CP initial concentration (20–80 mg/L), and NiO/sludge dosage (10–40 mg/100 mL). The maximum 2-CP degradation of 98% was reached at 50℃, pH 4, 50 mg/L 2-CP, and 0.3 g of NiO/sludge within 3 h of the reaction process. Under the appropriate circumstances, the optimal cation is exchanged among 2-CP molecules and the surface-active NiO/sludge adsorbent sites. This discovery observed that abundant waste sludge from conventional wastewater treatment plants can be further investigated and used as potential natural adsorbent material for the treatment of industrial effluents.